How useful is tandem language learning? Forms, potentials and limits of tandem work in e-tandem learning in university language courses - Adamczak-Krysztofowicz, Sylwia (Glottodidactica, 2018)
This article focuses on a German-Polish e-tandem course between Adam Mickiewicz University Poznań and the Technical University of Darmstadt, which was conducted as a joint cooperation seminar in real time on both sides. As part of the tandem project, students of Applied Linguistics in Poznań and students of the Darmstadt Language Centre created and presented their own video podcasts in mixed German-Polish tandems. The author discusses possible forms of language learning tandems and the main achievements of language e-tandem DaPo-cooperation on the basis of a quantitative and qualitative analysis of the students’ questionnaires. After the initial conclusions, the author formulates new questions that may help to develop an innovative e-tandem model for university language courses.